If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 37 = 12 + -62 Reorder the terms: 37 + 3x = 12 + -62 Combine like terms: 12 + -62 = -50 37 + 3x = -50 Solving 37 + 3x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + 3x = -50 + -37 Combine like terms: 37 + -37 = 0 0 + 3x = -50 + -37 3x = -50 + -37 Combine like terms: -50 + -37 = -87 3x = -87 Divide each side by '3'. x = -29 Simplifying x = -29
| -9m=-8m-4 | | -7r+6t=-16 | | 11+18b=19b | | 9=0.5(-9.81)(x^2) | | -9y+5=-7-7y | | -5v-4=-7v | | 53a-55=42 | | -(q+10)=-20 | | =x^2+20x-19 | | 10p-18p+-14=18 | | -30=-2(3c-7) | | x+x-30=2x | | -9-6q=6-9q | | 2w+9ifw=15 | | 3v-12=4v | | 8(1r-12d)= | | -19+3g=5g+17 | | d/3−6=19 | | 5q+7=34 | | 10-14j=-12j | | 3g+-7=8 | | -1y^2-3=-y^2-y-3 | | -4(k-17)=0 | | 0.08x+0.11(3x+37000)=18290 | | 12d+6=9d | | -9-4K=-1-5k | | 1x/2x-1/10x=1/5-1/4 | | 4p=6p-16 | | -3(m-12)=-12 | | 81*.15= | | 12+c=-2c | | -4(x-3)=x |